Mixed and integral feeding systems in the growth stage of guinea pigs (Cavia porcellus) of Peru, Andina and Inti breeds - Reynaga Roja, Max Fernando (2020)
The aim of this study was to determine the effect of the feeding system on the productive performance of growing guinea pigs of Peru, Andina and Inti breeds, reared under conditions of the central coast of Peru. A completely randomized design of six treatments in a factorial arrangement of 2x3 was used, having as factors two feeding systems (Integral: balanced food with vitamin C plus water; and Mixed: balanced food with vitamin C, green forage and water) and three breeds (Peru, Andean and Inti). Higher final weights and daily weight gains were obtained in the treatments with guinea pigs breed Peru with mixed (1010.3 g and 15.31 g) and integral feeding system (991.9 g and 14.61 g), respectively, with respect to the other treatments (p<0.05); while feed consumption in dry matter and carcass yield were statistically higher in the Peru group with mixed feeding (48.10 g DM/day, 72.77%). The most efficient feed conversion (p<0.05) was determined in the integral feeding system with Peru (2.73) and Andina (2.78) guinea pigs. The integral feeding systems registered less consumption and more efficient feeding conversion (p<0.05) compared to the mixed system.